Mexican-origin parent and child reported neighborhood factors and youth substance use - Zhen-Duan, Jenny; Banks, Devin E.; Ferreira, Caroline; Zhang, Lulu; Valentino, Kristin; Alegría, Margarita (Frontiers in Psychiatry, 2023)
Background: Structural oppression affects health behaviors through residence in suboptimal neighborhoods and exposure to community violence. Youth and parents report perceptions of neighborhood factors that affect youth substance use behaviors. Given that Latinx youth report higher levels of perceived community violence than other racial and ethnic groups, it is imperative to examine how youth-and parent-perceived neighborhood-level factors may relate to youth substance use. Methods: Data were collected using clinical interviews with family triads (fathers, mothers, and youth) and parent-child dyads (father or mother and youth) enrolled in the Seguimos Avanzando study of 344 Mexican-origin families in Indiana. Neighborhood measures, including perceptions of exposure to violence, neighborhood characteristics, and neighborhood collective efficacy, were included in parent and youth surveys. Self-report measures for past year alcohol and drug use were included in the youth survey only. T-tests were conducted to estimate differences in neighborhood reports among the sample triads. A series of linear regression models were used to estimate the associations between youth-, mother-, and father-reported perceptions of neighborhood factors and youth substance use. Results: Preliminary results indicate that fathers reported higher levels of exposure to violence than mothers (t(163)=2.33, p=.02) and youth (t(173)=3.61, p<.001). Youth reported lower negative neighborhood characteristics than mothers (t(329)=6.43, p<.001) and fathers (t(169)=3.73, p<.001). Youth reported significantly better neighborhood collective efficacy than mothers (t(296)=3.14, p=.002), but not statistically different from fathers. Results from the primary analysis showed that youth exposure to violence was positively associated with youth substance use (b=0.24, SE=0.06, p<.0001), but the youth's neighborhood characteristics and collective efficacy were not significantly associated with youth substance use. None of the parent-reported neighborhood variables were associated with youth substance use. The discrepant findings between parent and youth reports of perceived neighborhood characteristics and substance use have important implications for researchers and community stakeholders, and for developing targeted interventions and prevention strategies. Our study highlights the need to address youth experience of community violence and to prioritize creating safe and inclusive neighborhood environments. Potential strategies include improving community resources, strengthening social support networks, promoting open communication about neighborhood risks, and fostering collaborative efforts to address substance use behaviors.